The effectiveness of an educational program based on conceptual theory in the achievement of rhetoric among students of Arabic language departments in the faculties of basic education (Journal of the College of Basic Education, 2025)
The current research aims to identify "the effectiveness of an educational program based on conceptual theory in the collection of rhetoric when students of Arabic language departments in the faculties of basic education", and to achieve the goal of the research followed the researchers procedures experimental approach, as the researchers adopted an experimental design with partial control, which is the design of the experimental and control groups with a post-test, the research community consisted of colleges of basic education in Iraqi universities and the number (12) college and chose the researchers intentionally College of Basic Education At the University of Mustansiriya the same for their research, has reached (66) male and female students of the second stage divided into two halls chosen randomly represented hall (3) experimental group by (33) male and female students, While Hall (2) represented the control group by (33) male and female students, the researchers rewarded between the students of the two research groups in the following variables: (chronological age, language ability test, rhetoric grades in the first semester), as for the two research tools, the researchers have prepared an achievement test according to the six levels of Bloom according to what emerged from the test map, as it included (50) paragraphs and the researchers verified the sincerity and stability of the test, and extracted the discriminatory forces, and the coefficients of difficulty of its paragraphs, as the researchers built a standard for correcting the achievement test and verified its sincerity after presenting it to a group of arbitrators and then applied the test after the students of the research sample, one of the researchers studied the two research groups during the duration of the experiment, experimental educational program and control regular program, It lasted a full semester for the academic year (2023-2024) To process the data statistically the T-test for two independent samples, and the alpha-Cronbach equation, and Pearson's correlation coefficient, and the difficulty equation and the discrimination force equation and by using the T-test for two independent samples, the following results were reached: -There is a statistically significant difference at the level of significance (0.05) between the average scores of the students of the two research groups in the collection of rhetoric in the post-test in favor of the experimental group -In light of the results of the research, the researchers concluded that the use of the educational program contributed to raising the level of academic achievement of students in rhetoric